Thermal fatigue load models for fatigue design of steel box girder bridges. (November 2022) - Wang, Chunsheng; Zhang, Peijie; Wu, Genshu; Li, Puyu
Abstract: Coupling with traffic loads, thermal loads can also contribute to the fatigue damage cumulation of bridges. Referring to traffic and wind fatigue load models, the concepts of two kinds of probabilistic thermal fatigue load models for the first system of steel box girder bridges were proposed. Specifically, the basic forms of the two models are 1) equivalent vertical temperature gradient models based on the damage equivalence rule and 2) the effect ratio curves based on a statistical analysis of thermal actions. Then, two design probabilistic thermal fatigue load models following the given procedures are set up using an extended dataset based on a 350-day long-term in-suit temperature monitoring, and parametric analysis on three damage equivalence factors including geometric features, design life, and degree of indeterminacy was conducted. To validate the proposed models and related approaches, two kinds of fatigue details in a case steel box girder bridge were evaluated. The results show that thermal effects on fatigue damage cumulation are significant and should be taken into consideration, and the proposed thermal fatigue load models are applicable for fatigue design and evaluation. Highlights: The methodologies and procedures for establishing two kinds of thermal fatigue load models for steel box girder bridges were set up. The design TFLMs were made based on temperature monitoring data, and the related damage equivalence factors were analyzed. The increase rate of fatigue damage considering coupling thermal and traffic loads is larger than 5%.